Thermal protection characteristics of polydimethylsiloxane-organoclay nanocomposite. (October 2017) - Smitha Alex, Ancy; Rajeev, R.S.; Krishnaraj, K.; Sreenivas, N.; Manu, S.K.; Gouri, C.; Sekkar, V.
Abstract: Polydimethylsiloxane (PDMS) polymers are promising candidates as thermal protection systems (TPS) for aerospace applications. In the present study, incorporation of organically modified nanoclay has been successfully employed to improve the properties of PDMS. The effect of 2% w/w of nanoclay on the mechanical and dynamic mechanical properties, thermal, flammability, and thermo-physical properties, hydrophobicity, gas permeability and erosion resistance characteristics of PDMS is investigated. XRD and TEM analyses reveal intercalated to exfoliated morphology for the nanocomposite. Mechanical properties, thermo-oxidative stability, limiting oxygen index, hydrophobicity and permeability show an increasing trend with nanoclay inclusion; whereas, thermo-physical properties remain unaffected. When compared to unmodified PDMS, the ablative properties viz . erosion rate, mass loss rate and heat of ablation of the nanocomposite are more favorable for application as TPS. Also, a substantial reduction in back wall temperature is obtained with the incorporation of nanoclay. This study demonstrates that PDMS-nanoclay composite has a promising potential as TPS for aerospace applications.